Contour optimisation of polygon shaft-hub connections for gearbox applications. (17th April 2023) - Schuster, Maximilian; Petersen, Detlev; Koppenhagen, Frank
In this work, we determine the optimal geometry of complex trochoid polygon contours with respect to the stresses occurring in the shaft-hub connection. For this purpose, we carried out FEM calculations to investigate the influence of the different contour types as well as the variable parameters eccentricity and number of carriers on the level of stress occurring in the connection. With that, we derived concrete design and dimensioning guidelines for the use of polygon contours as a shaft-hub connection. Subsequently, we compared the static and dynamic load bearing capacity of a polygon connection designed according to these guidelines with a feather key connection by means of empirical tests and analytical calculations. It was shown that the H-contour is a particularly suitable solution. It showed low stress levels in the FEM calculations, and a higher static and dynamic load bearing capacity than the feather key connection in the empirical tests.